THE DISCURSIVE CONSTRUCTION OF INDIGENOUS BELIEF ISSUE IN THE JAKARTA POST - Suprayogi Suprayogi; Dian Puspita; Sandi Nuansa; Kamelia Sari (Universitas Islam Sumatera Utara (UISU), 2021)
As indigenous belief acknowledgement in Indonesia is still progressive, debatable but limitedly investigated from critical discourse analysis perspective, this research is aimed at revealing the discursive construction of indigenous belief issue in The Jakarta Post. This research focuses on analyzing indigenous belief as phenomenon, indigenous believers and government as social actor through the analysis of nomination and predication strategies. Articles published in The Jakarta Post online newspaper from 2013 - 2020 are chosen as corpus data. To analyze this research, Discourse-Historical Approach by Wodak and Meyer (2009) is used as the framework. This research also employs corpus analysis using Sketch Engine. The finding suggests that the issue centralized in the discussion of identity card and human right framed in five different periods. The use of collective proper name, anthroponym and deixis are significant to refer to indigenous believers, meanwhile institutional name, anthroponym and synecdoche are mostly used as referent for government. There is a shift of predication strategies from negative to positive when it discussed government policy on putting indigenous belief column on identity card. This research suggests that the use of corpus software as well as manual corpus screening is important to locate more detail language data.